Impact of perceived factors of coronavirus infection on COVID-19 vaccine uptake among healthcare workers in Ghana—Evidence from a cross-sectional analysis - Emmanuel K. Gelyi; John Azaare; Nana Kobea Bonso; Mary Rachael Kpordoxah; Gifty Apiung Aninanya (PLoS ONE, 2025)
Introduction Ghana faced acute COVID-19 vaccine uptake rejection after the rollout of the initial dose, thus, posing a risk of not reaching herd immunity as necessary to curb the spread of the novel coronavirus disease. Objective In this study, we analysed the impact of perceptions of the COVID-19 infection on COVID-19 vaccine uptake among healthcare workers in the Mampong district of Ghana. Methods The study was conducted between April 2022 and June 2023 and interviewed 260 respondents using a closed-ended electronic questionnaire in a Google form format. We then analysed for association using a composite outcome response of healthcare workers in Ghana using a multiple logistics regression model. The alpha value was set at p <  0.05 for statistical significance employing statistical software, IBM Statistical Package for the Social Sciences software. The analysis adjusted for independent covariates using respondent medical history, COVID-19 infection status, and sociodemographic characteristics. Results Out of the total respondents, 219 (84.2%) took at least one shot of a COVID-19 vaccine. Of those who took a vaccine, 61.9% took AstraZeneca, followed by Johnson and Johnson (8.5%) and Pfizer BioNTech (6.2%). Vaccine uptake was significantly associated with positive previous vaccination history (p <  0.001), perceived vaccine safety (p <  0.001), perceived seriousness of COVID-19 infection (p < 0.008), and trust in COVID-19 vaccine based on recommendations by experts (p <  0.015). Conclusion Previous vaccination history and perceived factors such as vaccine safety, the seriousness of the COVID-19 infection, perceived risk of infection, and trust in expert recommendations influenced vaccine uptake among healthcare workers in Ghana.